Complete genome sequence of a new bipartite begomovirus infecting cotton in the Republic of Benin in west Africa - Leke, W.N.; Khatabi, B.; Mignouna, Djana B.; Brown, J.; Fondong, V.N. (Springer, 2016)
Here, we report the complete genome sequence of a novel bipartite begomovirus isolated from cotton plants (Gossypium raimondii, Malvaceae) exhibiting light yellow mosaic symptoms. The genome sequence was determined by Illumina DNA sequencing and confirmed by Sanger sequencing of RCA-enriched, cloned circular genomic components. The DNA-A and DNA-B components were each ~2.7 kb in size, and their genome arrangement was characteristic of other Old World bipartite begomoviruses. While the DNA-A component was most closely related to tobacco leaf curl Comoros virus (TbLCKMV) at 80 %, the DNA-B component had as its closet relative soybean chlorotic blotch virus (SbCBV) at 66 %. This previously undescribed begomovirus is herein named “cotton yellow mosaic virus” (CYMV).